Glee. The final season [videorecording (DVD)] - Murphy, Ryan, 1965-; Colfer, Chris, 1990-; Lynch, Jane, 1960-; Michele, Lea; Morrison, Matthew, 1978- (20th Century Fox Home Entertainment, 2015)
In the exhilarating, heart-rending final season, club favorites reunite and a new group of young performers takes center stage. Following her disastrously short sitcom career, Rachel returns to McKinley High to find Principal Sue Sylvester trampling the arts, including the glee club. Without missing a beat, Rachel and a newly single Kurt set out to revitalize New Directions, hoping for a shot at the national title.